Case Report: Upadacitinib for SAPHO syndrome with biologics-induced paradoxical manifestation and Hyperimmunoglobulinemia E - Liu, Yuxi; Jin, Di; Li, Wen; Zhang, Shiqi; Li, Chen; Li, Xin (Frontiers in Immunology, 2026)
BackgroundSAPHO (synovitis, acne, pustulosis, hyperostosis, and osteitis) syndrome is a rare autoinflammatory disease. Paradoxical reactions and immune deviation following biologic therapy are occasionally observed in clinical practice; however, to our knowledge, no previous cases of paradoxical skin rash accompanied by Hyperimmunoglobulinemia E have been reported.Case presentationA 35-year-old male with SAPHO syndrome experienced significant exacerbation of palmoplantar pustulosis and a sharp increase in immunoglobulin E(IgE) levels following treatment with secukinumab and infliximab. After one month of upadacitinib therapy, the patient showed marked improvement in cutaneous lesions and bone pain, along with significant normalization of inflammatory markers and a pronounced reduction in IgE levels.ConclusionThis case suggests that upadacitinib may be a valuable therapeutic option for patients with refractory SAPHO syndrome, particularly those presenting with paradoxical reactions or hypersensitivity. The unique mechanism of action of Janus kinase (JAK) inhibitors may offer superior efficacy in such cases, though further clinical validation and mechanistic studies are warranted.